Molecular dynamics simulation on micro-explosion of water-in-oil droplets in presence of solid particles or electric field. (1st November 2022) - Wei, Mingrui; Yang, Shuwen; Ju, Hongling; Guo, Guanlun
Highlights: Micro-explosion processes were simulated by molecular dynamics. The presence of solid particles or an electric field can facilitate micro-explosion. Adding solid particles can weaken the potential restriction on water molecules. The effect of external electric field is caused by the reduction of electrostatic potential. Abstract: The effects of solid particles or external electric field on the whole micro-explosions, especially bubble nucleation, were explored by molecular dynamics simulation. The corresponding reasons are also revealed. For this purpose, a water-in-oil droplet in nitrogen environment were constructed and the whole micro-explosion processes were simulated. Bubble nucleation time and nucleation temperature were estimated and compared with the cases in presence of solid particles or an electric field. The energy, force and coordination number of the water sub-droplet were explored to clarify the effects of the solid particles or an electric field. Results indicate that the presence of solid particles or an electric field can shorten the nucleation time and lower nucleation temperature, which are effective ways to control the micro-explosion process. Adding solid particles can weaken the potential restriction on water molecules, which much facilitates water molecules evaporations, and the effect is positive correlation with solid particle sizes. The effect of an external electric field on micro-explosion is essentially caused by the reduction of electrostatic potential. In the alternating electric field case, the reason for the faster temperature rise and the shorter nucleation time is that the sinusoidal change of the electrostatic force.